THE ROLE OF CRITICAL THINKING IN LEARNING A FOREIGN LANGUAGE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article is devoted to the topic of critical thinking in learning a foreign language. In the process of teaching a foreign language it is necessary to implement elements of technology to develop critical thinking by students. The main task of students is to learn effectively, to find knowledge, to think critically. They need to carefully understand, comprehend, and learn new information. It is also important to understand the different perspectives to understand, to understand, to understand the concept, to question the idea a little, to check if individual ideas can be used.